Inflammatory Alterations to Renal Lymphatic Endothelial Cell Gene Expression in Mouse Models of Hypertension - Justin G. McDermott; Bethany L. Goodlett; Heidi A. Creed; Shobana Navaneethabalakrishnan; Joseph M. Rutkowski; Brett M. Mitchell (Karger Publishers, 2024)
Introduction: Hypertension (HTN) is a major cardiovascular disease that can cause and be worsened by renal damage and inflammation. We previously reported that renal lymphatic endothelial cells (LECs) increase in response to HTN and that augmenting lymphangiogenesis in the kidneys reduces blood pressure and renal pro-inflammatory immune cells in mice with various forms of HTN. Our aim was to evaluate the specific changes that renal LECs undergo in HTN. Methods: We performed single-cell RNA sequencing. Using the angiotensin II-induced and salt-sensitive mouse models of HTN, we isolated renal CD31+ and podoplanin+ cells. Results: Sequencing of these cells revealed three distinct cell types with unique expression profiles, including LECs. The number and transcriptional diversity of LECs increased in samples from mice with HTN, as demonstrated by 597 differentially expressed genes (p < 0.01), 274 significantly enriched pathways (p < 0.01), and 331 regulons with specific enrichment in HTN LECs. These changes demonstrate a profound inflammatory response in renal LECs in HTN, leading to an increase in genes and pathways associated with inflammation-driven growth and immune checkpoint activity in LECs. Conclusion: These results reinforce and help to further explain the benefits of renal LECs and lymphangiogenesis in HTN.